PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE DALAM UPAYA PENINGKATAN HASIL BELAJAR DAN AKTIVITAS SISWA PADA MATERI PERSAMAAN LINIER SATU VARIABEL - Fitriani Fitriani; Yuni Rhamayanti; Adek Nilasari Harahap (JURNAL MathEdu (Mathematic Education Journal), 2021)
This research is a Classroom Action Research. In this research, learning tools are arranged: Lesson Plans, Teacher's Guidebooks and Student Worksheets. Next, arrange essay test instruments and student observation sheets, before the test instruments are used, they are tested first and the results are used for research instruments. This research was carried out through 2 cycles before being given action, first given a diagnostic test with a minimum category of enough to get 40.91%. Furthermore, given a test of mathematics learning outcomes in the first cycle, it was 77.27 which increased to 86.36 in the second cycle. The percentage of active student activity increased, this was obtained from the average level of student activity in the first cycle of 76% then in the second cycle it rose to 85.28. The teacher's ability to manage learning cycle I and cycle II is included in the "Good" category. Based on these results, this study suggests the application of the Think Pair Share learning model to improve students' mathematics learning outcomes in class VII-3 of SMP Negeri 2 Batahan.